Post-kala-azar dermal leishmaniasis with mucosal involvement: an unusual case presentation including successful treatment with Miltefosine - Salam, Md. Abdus; Siddiqui, Muhammad Afsar; Nabi, Shah G; Bhaskar, Khondaker Rifat Hasan; Mondal, Dinesh (International Centre for Diarrhoeal Disease Research, Bangladesh, 2013)
Post-kala-azar dermal leishmaniasis (PKDL) is a dermatologic manifestation that usually occurs after visceral leishmaniasis (VL) caused by Leishmania donovani. It is characterized by hypopigmented patches, a macular or maculopapular rash and nodular skin lesions on the body surface. Involvement of the mucosae is very rare and unusual in PKDL. We report a case of PKDL that presented with polymorphic skin lesions, along with involvement of peri-oral mucosa and tongue from an endemic area for kala-azar in Bangladesh. In the absence of a definite past history of kala- rapid serological tests against two recombinant (rK39 and rK28) leishmanial antigens, demonstration of Leishmania donovani (LD) body in the slit skin smear, and isolation of promastigotes by culture from a nodular lesion. The patient was treated with oral Miltefosine for three consecutive months and showed significant clinical improvement as demonstrated by a negative slit skin smear at two months after initiation of therapy. We report this case as an unusual presentation of mucosal involvement in PKDL and subsequent treatment success with Miltefosine.